Female and Male auto- and heterostereotypes of Russian and Belarusian youth - M. M. Karnialovich; V. I. Kazarenkov (Вестник университета)
The article is devoted to the actual problem of the social cognition psychology: stereotyping as a mechanism of interpersonal perception and self-perception in the context of the biological sex of the subject and the object of social perception. The results of an empirical study of male and female auto- and heterostereotypes of young women and young men, performed on a combined (Russian-Belarusian) sample, are presented. Content features and modality (emotional coloring) of male and female auto- and heterostereotypes were revealed using a free associative experiment. The content and structure of male and female auto- and heterostereotypes that exist in the ordinary consciousness of modern youth have been determined and analysed. Based on the results of the correlation analysis, the strength, direction and meaningful characteristics of the relationship between auto- and heterostereotypes in the male and female samples have been revealed. The results of the study are of interest to specialists in the field of psychology of social cognition, differential psychology, social psychology of personality, psychology of heterosexual relationships.